Management and Organization Review Second Research Frontiers Conference III: The Coevolution of SMEs and Family Firms in Russia, Ex-Soviet Republics, and Eastern European Economies: Knowledge Creation, Entrepreneurship, Innovation, and Economic Growth. (28th December 2016) - Unknown
Abstract : We are excited to announce the third conference of the Management Organization Review (MOR) Second Research Frontiers Conference Series. Whereas the first two conferences focused on China and India, the Rotterdam conference shifts focus to Russia, Ex-Soviet Republics, and Eastern Europe. This interdisciplinary Research Frontiers Conference serves as a key MOR exploration dialectic for advancing and opening new research directions of phenomena in the social sciences underlying management and organizations, globalization, and economic growth through boundary-crossing dialog and discourse with a focus on all transforming economies.